Alterações neuroimunológicas induzidas pela exposição ocupacional a agrotóxicos em mulheres da região do sudoeste do Paraná - Rossi, Maiara Grasiela (2022)
Brazil is one of the world's major agricultural producers, as a result, the use of pesticides in the country is also highlighted. These agrochemicals have the function of inhibiting pests that harm the plantation, thus intensifying production. On the other hand, contact with pesticides can bring acute and chronic damage to human health. Since living near plantations, the practice of spraying and even washing clothes after this activity, has occupationally exposed residents and rural workers, who also because of this each year are more sick, making this occupational contact a major problem for the public health service. One of the possible damage to human health resulting from this exposure is the dysregulation of the hypothalamus axis, which in itself is directly associated with the emergence of mental disorders, such as anxiety and depression. For this reason, this study aimed to verify the relationship between occupational exposure to pesticides and possible signs and symptoms of depressive disorders, as well as their neurological biomarkers, in addition to the immunological and endocrine profile of women living in the Southwest region of Paraná, comparing an occupationaland non-exposed group. This study was conducted with women attended at the Cancer Hospital in Francisco Beltrão, the selected women were those who did not present a diagnosis of any type of malignant neoplasms, which may be exposed to pesticides or not. We then sought through a questionnaire applied via telephone or whatsapp, answered through google questions, in order to analyze the profile of this exposure, as well as signs and symptoms of anxiety and depression (through the HADS scale), or also identify those women already diagnosed by a professional with any of these mental disorders. From this stage, some biomarkers were analyzed and measured in the plasma of the participants that could help answer the initial question and trace the neuroimmunological profile of these individuals; biomarkers such as: Interleukin 6 (iL-6), Interleukin 1β (il-1β), Brain-Derived Neurotrophic Factor (BDNF) and biomonitoring of colinesterase activity. The result for the scores ofthe questionnaire suggests that exposure to pesticides is correlated with the development of anxiety and depression in the agricultural population. The analysis of biological markers showed statistical differences for the activity of butyrylcholinesterase (BuChE) and between the groups of women exposed and not exposed topesticides. It is then concluded through the results obtained through questionnaires and biochemical measures, it is observed that women characterized as exposed to these products harmful to health, present increased risk for the development of mental disorders, as well as anxiety and depression.